Biochemical profiling of anti-HIV prodrug Elsulfavirine (Elpida®) and its active form VM1500A against a panel of twelve human carbonic anhydrase isoforms. (1st January 2021) - Supuran, Claudiu T.; Nocentini, Alessio; Yakubova, Elena; Savchuk, Nikolay; Kalinin, Stanislav; Krasavin, Mikhail
Abstract: The non-nucleoside reverse transcriptase inhibitor VM1500A is approved for the treatment of HIV/AIDS in its N -acyl sulphonamide prodrug form elsulfavirine (Elpida ® ). Biochemical profiling against twelve human carbonic anhydrase (CA, EC 4.2.1.1) isoforms showed that while elsulfavirine was a weak inhibitor of all isoforms, VM1500A potently and selectively inhibited human (h) h CA VII isoform, a proven target for the therapy of neuropathic pain. The latter is a common neurologic complication of HIV infection and we hypothesise that by using Elpida ® in patients may help alleviate this debilitating symptom. Graphical Abstract: UF0001